Sensory urban mapping: a case study of Istiklal Street, Istanbul with the method of 'sensewalking' - Kartal, Asiye Nisa (2021)
The 'sensory' plays a vital role in examining human and world interrelations if often overlooked. This thesis aims to have a new understanding of Istiklal Street, Istanbul, through the area's sensory qualities. The research is grounded on a 'phenomenological' approach and intends to move beyond the urban visual experiences by looking into the area's multi-sensory experiences. The practice of 'sensewalking' has been used in research to cope with visually-oriented urban assessments. This investigation, which is structured with a qualitative lens to discover the Street's sensory aspects, would be worthwhile primarily for the fields of architecture, urban sensory design. As we see, the changing socio-cultural structure, economic and political movements, law regulations, innovative transportation and communication activities have resulted in a controversial modification of Istanbul in recent years. On Istiklal Street, Istanbul's culture, entertainment, tourism focus, many buildings were restored, moved, converted, closed, and demolished after the 1990s. All have been significant elements in terms of the qualitative value of this area. Many debates have been put forward by social scientists, urban planners, and architects about Istiklal Street's transformation. Except for the field of academic discussions, the enormous amounts of discourses in social media have shown that the multi-layered socio-cultural and architectural structure of Istiklal Street has been changing dramatically in a controversial way. This thesis supports the idea that while Istiklal Street has changed, the transformation has not been only spatial, socio-cultural, or economic. The research claims that the sensory experiences which have great importance in terms of intangible qualities of this area have begun to lose their distinctive features. Therefore, the research has focused on the individually sensed and assessed sensory qualities on the Street beyond the visual experiences. With the way of 'mapping', collected data of the sensewalking-based fieldworks has been presented. As the primary assessment, the research claims that Istiklal Street's sensory dimensions deserve to be recorded and decoded as expeditiously as possible to observe the sensory reflections of transformations in the area. The research findings showed that Istiklal Street's latest modifications and adjustments had arguably influenced this place's sensory qualities. The result says sensory stimuli of the place are connected, and the sensory elements create a specific sensory ambience. Moreover, the sensory interaction in the place is infected by the physical or spatial changes in the area. This research offers convincing evidence for the argument that the sensory composition of the urban place should not be considered separately from its non-visual characteristics. Istiklal Street's sensory consideration needs to be embedded in further investigations and applications. Increasing awareness about urban places' distinctive sensory qualities and Sensemarks is worthwhile. The inhabitants' sensory urban experiences provide new insights to comprehend urban places. The research method, ‘sensewalking’, produced an unconventional, novel attitude in the context of qualitative-based urban studies to see the sensory reflections of the physical urban transformations. The research's findings opened creative and productive ways for architecture, urban design, planning, urban ethnography, and intangible heritage studies.